A Prospective Randomized Double-Blinded Controlled Study of Ropivacaine 0.75% Versus Bupivacaine 0.5%-Mepivacaine 2% for Peribulbar Anesthesia. Issue 2 (1st March 2000) - Luchetti, Marco; Magni, Giuseppe; Marraro, Giuseppe
Abstract : Background and Objectives: Ropivacaine 1% has recently been used in clinical trials for peribulbar anesthesia. This study aims to compare the safety and the efficacy of ropivacaine 0.75% with that of a 1:1 mixture of bupivacaine 0.5% and mepivacaine 2% for peribulbar anesthesia. Methods: Two thousand patients undergoing peribulbar anesthesia for elective cataract phacoemulsification were prospectively studied over a 1-year period and randomly assigned to 1 of 2 groups according to the local anesthetic used. One thousand patients were administered peribulbar anesthesia with 9 mL of ropivacaine 0.75% plus 1 mL of hyaluronidase (group R), and 1, 000 patients received peribulbar anesthesia with 4 mL of bupivacaine 0.5% plus 4 mL of mepivacaine 2% plus 1 mL of hyaluronidase plus 1 mL of sodium bicarbonate (group BM). Peribulbar anesthesia was always accomplished by the same physician by 2 injections of 5 mL each, with a 25-gauge 25-mm needle. Evaluation was performed by another physician blinded to the technique used and included assessment of pain on local anesthetic injection, ocular and eyelid akinesia, need for top-up injections, onset time and duration of anesthesia, intraoperative analgesia, duration of surgery, hemodynamic parameters, and incidence of perioperative complications. Results: A greater incidence of pain on injection was found in group BM (P < .001). No difference between the groups was found regarding the onset time and the duration of anesthesia. Perioperative analgesia was satisfactory in both groups with no significant difference. Patients in group R showed a reduced need for top-up injection and a better ocular akinesia at 8 and 10 minutes (P < .01). The akinesia of the eyelid was comparable in the 2 groups and complete in all cases at 8 minutes. Cardiac arrhythmias were more frequent in group BM (P < .01). Local complications did not differ between the groups. An increase in mean artierial blood pressure and heart rate was observed in both groups 1 minute after injection of local anesthetic. Conclusions: Peribulbar anesthesia with ropivacaine provided better ocular akinesia 8 to 10 minutes after block insertion than a bupivacaine-mepivacaine mixture, which reduced the need for top-up injections. Ropivacaine also caused less pain on injection.